Antimicrobial resistance and genomic investigation of non-typhoidal Salmonella isolated from outpatients in Shaoxing city, China - Chen, Jiancai; Ed-Dra, Abdelaziz; Zhou, Haiyang; Wu, Beibei; Zhang, Yunyi; Yue, Min (Frontiers in Public Health, 2022)
Human non-typhoidal salmonellosis is among the leading cause of morbidity and mortality worldwide, resulting in huge economic losses and threatening the public health systems. To date, epidemiological characteristics of non-typhoidal Salmonella (NTS) implicated in human salmonellosis in China are still obscure. Herein, we investigate the antimicrobial resistance and genomic features of NTS isolated from hospitalized patients in Shaoxing city in 2020. Eighty-seven Salmonella were isolated and have been tested against 28 different antimicrobial agents, representing 12 categories. The results showed high resistance to cefazolin (86.21%), streptomycin (81.61%), ampicillin (77.01%), ampicillin-sulbactam (74.71%), doxycycline (72.41%), tetracycline (71.26%), and levofloxacin (70.11%). Moreover, 83.91% of isolates were resistant to ≥3 categories which were considered multi-drug resistant (MDR). Whole-genome sequencing (WGS) combined with bioinformatic analysis was used to predict serovars, MLST types, plasmid replicons, antimicrobial resistance genes, and virulence genes, in addition to the construction of phylogenomic to determine the epidemiological relatedness between isolates. Fifteen serovars and 16 STs were identified, with the dominance of S. 4,[5],12:i:– ST34 (25.29%), S. Enteritidis ST11 (22.99%), and S. Typhimurium ST19. Additionally, 50 resistance genes representing 10 categories were detected with the high prevalence of aac(6')-Iaa (100%), blaTEM-1B (65.52%), and tet(A) (52.87%), encoding resistance to aminoglycosides, β-lactams, and tetracyclines, respectively; in addition to chromosomic mutations affecting gyrA gene. Moreover, we showed the detection of 18 different plasmids with the dominance of IncFIB(S) and IncFII(S) (39.08%). Interestingly, all isolates harbor the typical virulence genes implicated in the virulence mechanisms of Salmonella, while one isolate of S. Jangwani contains cdtB gene encoding typhoid toxin production. Furthermore, the phylogenomic analysis showed that all isolates of the same serovar are very close to each other and clustered together in the same clade. Together, the high incidence of MDR among the studied isolates is alarming for public health services and efforts should be gathered to further introduce WGS in routinely monitoring of AMR Salmonella in medical field.